(untitled) (Fiep Bulletin - online, 2014)
This article has the intention to bring the professionals of education and in a particular way to the Physical Education ones, to the responsibility that fits to each one in the creation of a society more humankind. In our pedagogical experiences we come across with situations that are presented in a favorable way to raise a playful culture in our pupils. This construction will effectively bring good contribution in the traffic between school/society, it can influence people to have a life toward the valuation of the human being, and that the playful is a safe bridge to this way of being materializes. We approach, even in a superficial way, the playful as a human feeling exclusively so that it is able to achieve by the human through a conscientious action. We talk about the questions of the academic formation of the professionals who act with possibilities to develop practical playful, showing the difficulty of the application of facilitator methodologies of human development for the playful, many times for the lack of status that this thematic presents, and for the little disposal of the teachers. Finally, we point in a personal form, the world that we could create, not as a utopia, but with the courage to dream and to carry through.